The Effect of Defensive Pessimism and Optimism on Failed Entrepreneurs’ Re-Entry İntention - Wijaya, Morgan Lorentz; Layman, Chrisanty Victoria (APMBA (Asia Pacific Management and Business Application), 2023)
This study aims to determine the factors that encourage entrepreneurs who have failed to show re-entry intention by focusing on the effect of optimism and defensive pessimism on the intention of their re-entry intention. In this study, entrepreneurs who have failed in sustaining their business will be the focus subject. This study uses the method of distributing questionnaires for data collection and processes it using SmartPLS 3.0 software by analyzing the outer model to test the convergent validity, discriminant validity, and reliability. The questionnaires were distributed through social media such as WhatsApp and Line. 278 respondents participated in this study which was conducted from August to October 2021. The results of this study showed career ambitions and public self-awareness have a positive impact on optimism, a negative relationship with fear of failure leads to pessimism, a positive relationship with self-doubt leads to defensive pessimism, and coping humor doesn’t have a moderating effect on the path from defensive pessimism and optimism to the intention to re-enter.